2006
DOI: 10.1111/j.1476-5829.2006.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of receptor tyrosine kinases VEGFR‐1 (FLT‐1), VEGFR‐2 (KDR), EGFR‐1, PDGFRa and c‐Met in canine primary brain tumours

Abstract: Inhibition of tumour growth and angiogenesis by targeting key growth factor receptors is a promising therapeutic strategy for central nervous system tumours. Characterization of these growth factor receptors in canine primary brain tumours has not been done. Using quantitative real-time TaqMan polymerase chain reaction (PCR), we evaluated the expression of messenger RNA (mRNA) for five tyrosine kinase growth factor receptors (vascular endothelial growth factor receptor [VEGFR]-1, VEGFR-2, endothelial growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 38 publications
(70 reference statements)
5
75
1
Order By: Relevance
“…Veterinary trials with toceranib and masitinib have shown benefit in several cancers but have not been reported for brain tumors. Documented overexpression of VEGF, VEGF receptors, and PDGFR alpha in some canine brain tumors108, 109, 110, 111, 112, 113, 114, 115, 116 may justify trials with these or similar small molecules in defined patients.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Veterinary trials with toceranib and masitinib have shown benefit in several cancers but have not been reported for brain tumors. Documented overexpression of VEGF, VEGF receptors, and PDGFR alpha in some canine brain tumors108, 109, 110, 111, 112, 113, 114, 115, 116 may justify trials with these or similar small molecules in defined patients.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…29,63,82 In contrast, in a population of 11 dogs with varying grades of astrocytoma, minimal increases in PDGFRa mRNA were detected in tumor tissue compared with controls. 16 Recently, overexpression of PDGFRa was demonstrated by tissue microarray immunophenotyping in 43% (3 of 7) of GBMs, 20% (1 of 5) of grade III canine astrocytomas, and 14% (1 of 7) of grade II canine astrocytomas. 26 In people with astrocytoma, the prognostic and predictive value of PDGFRa expression within tumor tissue is controversial and clouded by inconsistencies in patient populations, analytic methods, and study design.…”
Section: Astrocytic Tumor Biomarkersmentioning
confidence: 99%
“…27 Both VEGFR-1 and VEGFR-2 mRNA have also been identified in astrocytic tumors from dogs, although among 23 kinds of canine astrocytic neoplasia, expression levels did not significantly differ on the basis of tumor grade. 16 In people, astrocytic tumor VEGF expression has not been shown to be an independent prognostic biomarker associated with survival. 21,30,40,55 The value of VEGF and VEGFR as predictive or prognostic biomarkers in dogs with astrocytic neoplasia has not been examined.…”
Section: Astrocytic Tumor Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations